HUBUNGAN MOTIVASI KERJA DENGAN KINERJA KARYAWAN AKPER PANTI KOSALA SURAKARTA - Endang Dwi Ningsih; Tri Susi Wulandari; Aan Daryanto (KOSALA : Jurnal Ilmu Kesehatan, 2015)
AbstractIntroduction: Motivation is the human psychological characteristics that contribute to a personal commitment’s level, these are included the causal factors, to aplicate and keep maintaining the human behavior into a certain purposed direction. Performance is someone working achievement. The motivation gives a significant contribution to increase the working performance of employees. The objective of the study: To know the relation between motivation with working performance of the Nursing Academy Panti Kosala Surakarta employees.The Subject of the study: The 33 person of the Nursing Academy Panti Kosala employees. Sampling technical used is saturated sampling, there for all of the subject are used as the sample.The datas are collected by questionnaire method for both variable, the motivation and the employees working performance, analyzed by Chi Square test.The result: By Chi Square test used SPSS for windows series 18 with α = 5 % ( 0.05) , the value of p = 0.000, ( p <0.05), is the hypothesis received. The study conclusion: There is any relation between motivation with working performance Nursing Academy Panti Kosala Surakarta employees.Keywords: Working motivation, employee performance